Biochemical Characterization of Kluyveromyces lactis Adenine Deaminase and Guanine Deaminase and Their Potential Application in Lowering Purine Content in Beer - Mahor, Durga; Prasad, Gandham S. (Frontiers in Bioengineering and Biotechnology, 2018)
Excess amount of uric acid in humans leads to hyperuricemia that is a biochemical precursor of gout and is also associated with various other disorders. Gout is termed as crystallization of uric acid, predominantly within joints. The burden of hyperuricemia and gout has increased worldwide due to lifestyle changes, obesity, and consumption of purine-rich foods, fructose-containing drinks, and alcoholic beverages. Some of the therapies available to cure gout are associated with unwanted side-effects and antigenicity. We propose an attractive and safe strategy to reduce purine content in beverages using enzymatic application of purine degrading enzymes viz. adenine deaminase (ADA) and guanine deaminase (GDA) enzymes that convert adenine and guanine into hypoxanthine and xanthine, respectively. Here we cloned, expressed, purified, and biochemically characterized both adenine deaminase (ADA) and guanine deaminase (GDA) enzymes that play important roles in the purine degradation pathway of Kluyveromyces lactis and their application in lowering purine content in a beverage. Popular beverage beer has been selected as an experimental sample as it confers higher risks of hyperuricemia and gout. Quantification of purine content in 16 different beers from the Indian market showed varying concentrations of different purines. Enzymatic treatment of beer samples with ADA and GDA showed a reduction of adenine and guanine content, respectively. These enzymes in combination with other purine degrading enzymes showed marked purine reduction in beer. Both enzymes can work at 5.0-8.0 pH range and retain >50% activity at 40 °C making them good candidates for industrial applications.